Comparison of the effect of oxygen supplementation using flow-by or a face mask on the partial pressure of arterial oxygen in sedated dogs. Issue 1 (2nd January 2019) - Wong, AM; Uquillas, E; Hall, E; Dart, CM; Dart, AJ
Abstract : AIMS: To compare the effect of oxygen supplementation using flow-by or a face mask on the partial pressure of arterial oxygen (PaO2 ) in sedated dogs. METHODS: Twenty healthy dogs weighing >15 kg, of mixed sex and breed, were enrolled in a randomised cross-over study. Each dog was sedated with I/M 0.015 mg/kg medetomidine and 0.5 mg/kg methadone. Twenty minutes later dogs were exposed to two 5-minute treatment periods of oxygen supplementation separated by a 15-minute washout period during which dogs were allowed to breathe room air. During the treatment periods, oxygen was delivered at a flow rate of 3 L/minute either through a face mask (face mask oxygenation), or via a tube held 2 cm from the dog's nares (flow-by oxygenation). The order in which the treatments were administered was randomised. Arterial blood was collected for blood gas analysis and rectal temperature measured at four times: prior to commencing treatments, after each treatment, and at the end of the 15 minutes washout period between treatments. RESULTS: The mean PaO2 in arterial samples taken from the dogs after face mask oxygen supplementation was 371.3 (SE 13.74) mmHg which was higher than in samples taken after they received flow-by oxygen supplementation (182.2 (SE 6.741) mmHg; p<0.001). The mean PaO2 in samples taken after receiving either form of oxygen supplementation was higher than in samples taken after the dogs had been breathing room air (82.43 (SE 2.143) mmHg; p<0.001). There was no association between sex, age, weight or breed of dogs and blood gas parameters or rectal temperature (p>0.05). CONCLUSIONS: Oxygen supplementation delivered using a face mask was more effective at increasing PaO2 than flow-by oxygen supplementation. Flow-by oxygen supplementation at a distance of 2 cm from the nose may be a suitable alternative when the use of a face mask is not tolerated by the patient.